Preliminary study on the correlation between accelerated current and dose in water for an electron-based LINAC - Franciosini, G.; Muraro, S.; De Gregorio, A.; De Simoni, M.; Di Francesco, M.; Di Martino, F.; Dong, Y.; Felici, G.; Galante, F.; Harold Pensavalle, J.; Marafini, M.; Mattei, I.; et al. (Frontiers in Physics, 2024)
Intra Operative Radio Therapy (IOeRT) is considered the first clinical translation of FLASH with electrons. A crucial aspect is represented by the precise dose monitoring and measurement; at this aim we propose a method fully based on Monte Carlo (MC) simulation that uses as input the beam current measurement and the beam optics simulation. To validate this approach we chose the NOVAC11 (produced by Sordina IORT Technologies SpA 1 ) accelerator, which provides a well-studied model.We used FLUKA and FRED MC software to simulate in detail the geometry of the NOVAC11 and the coupled applicator usually adopted in clinical practice to deliver the dose in the surgical bed. The simulation results of the longitudinal and Off-axis profiles, and dose per pulse obtained in a water phantom with different applicators are compared to the experimental data.iA very good agreement not only for the relative dosimetry in both the longitudinal and off-axis profiles, with a gamma index pass rate of 100% with 3%/3 mm acceptance criteria but also for the absolute dosimetry was obtained.Conclusions: The results completely validate the MC description of the system and provide a reliable evaluation of the dose per pulse and output factor with an accuracy of the order of few % for different sets of applicator diameters and lengths.